Multikulturalisme di Ruang Urban: Dinamika Politik Perkotaan dan Peran SETARA Institute dalam Kasus Intoleransi terhadap Minoritas Agama - Cendana Anabel; Naura Rania Bari; Silvia Zahra Zahira; Aniqotul Ummah; Chomariyana Kartika Hesti (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Urban spaces are often imagined as inclusive environments where diverse religious identities coexist. In reality, urban political dynamics, power distribution, and relations between majority and minority groups frequently create unequal recognition toward religious minorities, leading to discrimination and intolerance. An analysis through Charles Taylor’s Politics of Recognition reveals how urban political dynamics shape religious intolerance and how SETARA Institute responds through advocacy efforts. A qualitative descriptive approach was used. Primary data were collected through semi structured interviews with the Coordinator of Indonesian Social Inclusion and Security Studies at SETARA Institute, while secondary data were obtained through documentation studies consisting of journals, books, news articles, and official publications from SETARA Institute. The findings show that intolerance in urban areas remains closely tied to exclusionary governance and weak institutional protection, placing minority groups in vulnerable positions. SETARA Institute strengthens advocacy through documenting violations of freedom of religion and belief, developing the Tolerant City Index, producing empirical research, and promoting human rights based policies.